Evolution of Thermoelectric Properties of Zn4Sb3 Prepared by Mechanical Alloying and Different Consolidation Routes - Pee-Yew Lee; Pei-Ho Lin (Energies, 2018)
In this research, a method combining the mechanical alloying with the vacuum sintering or hot pressing was adopted to obtain the compact of β-Zn4Sb3. Pure zinc and antimony powders were used as the starting material for mechanical alloying. These powders were mixed in the stoichiometry ratio of 4 to 3, or more Zn-rich. Single phase Zn4Sb3 was produced using a nominally 0.6 at. % Zn rich powder. Thermoelectric Zn4Sb3 bulk specimens have been fabricated by vacuum sintering or hot pressing of mechanically alloyed powders at various temperatures from 373 to 673 K. For the bulk specimens sintering at high temperature, phase transformation of β-Zn4Sb3 to ZnSb and Sb was observed due to Zn vaporization. However, single-phase Zn4Sb3 bulk specimens with 97.87% of theoretical density were successfully produced by vacuum hot pressing at 473 K. Electric resistivity, Seebeck coefficient, and thermal conductivity were evaluated for the hot pressed specimens from room temperature to 673 K. The results indicate that the Zn4Sb3 shows an intrinsic p-type behavior. The increase of Zn4Sb3 phase ratio can increase Seebeck coefficient but decrease electric conductivity. The maximum power factor and figure of merit (ZT) value were 1.31 × 10−3 W/mK2 and 0.81 at 600 K, respectively. The ZT value was lower than that reported in the available data for materials prepared by conventional melt growth and hot pressed methods, but higher than the samples fabricated by vacuum melting and heat treatment techniques.